Notes on the occurrence and habitats of sabethes purpureus in salta province, Argentina - Mangudo, Carolina (2014)
The finding of Sabethes purpureus larvae and pupae in tree holes both in urban and forest environments in San Ramón de la Nueva Orán, Salta Province, Argentina, is reported, together with information on the larval habitat. Tree holes were sampled monthly from January to March or April of 2011, 2012, and 2013 along sidewalks, in public access areas, and in 3 sites within forested areas outside the city, selected along an urban gradient in Orán. Sabathes purpureus was most frequently found in low numbers and with other mosquito species. A higher proportion of tree holes was positive in the urban compared to the forest environment, although there were no significant differences in abundances or densities per hole. To our best knowledge, this paper reports the species for the first time breeding in an urban environment, and extends its geographical distribution from the Atlantic and Paranaense forests to the Southern Andean Yungas in northwestern Argentina.